2009
DOI: 10.1354/vp.46-2-299
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pathology of Nocardiosis in Marine Mammals

Abstract: Abstract. Nocardia spp. infections in mammals cause pyogranulomatous lesions in a variety of organs, most typically the lung. Members of the Nocardia asteroides complex are the most frequently recognized pathogens. Nine cases of nocardiosis in free-ranging pinnipeds and 10 cases of nocardiosis in cetaceans were evaluated. Host species included the hooded seal (Cystophora cristata, n 5 8), leopard seal (Hydrurga leptonyx, n 5 1), Atlantic bottlenose dolphin (Tursiops truncatus, n 5 4), beluga whale (Delphinapte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 45 publications
1
21
0
1
Order By: Relevance
“…The age of present case is consistent with the literature implying that Nocardia is primary pathogen for the young dog; hence 34 of 52 dogs, 65.40% were less than 1 year of age [2]. Similarly, juvenile marine mammals were reportedly affected more than the adult animals [3]. The primary differential diagnosis for the present case include Toxoplasma gondii, fungal and mycobacterial infections.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The age of present case is consistent with the literature implying that Nocardia is primary pathogen for the young dog; hence 34 of 52 dogs, 65.40% were less than 1 year of age [2]. Similarly, juvenile marine mammals were reportedly affected more than the adult animals [3]. The primary differential diagnosis for the present case include Toxoplasma gondii, fungal and mycobacterial infections.…”
Section: Resultssupporting
confidence: 84%
“…Nocardiae are nonmotile, facultatively intracellular pathogen in humans and, domestic and wild animals. Furthermore, they cause significant infections in cats, horses, goat, sheep, pigs, fish, birds, marine mammals and a variety of wild and zoo animals [13]. The other and separate form of disease is the bovine mastitis occuring in dairy cattle and also it progresses into systemic infection [1].…”
Section: Introductionmentioning
confidence: 99%
“…As a follow up to UME dolphins in which bacterial pathogens were suspected in the lung, lung samples from five dolphins were tested for the presence of bacterial pathogen DNA using a commercially available kit (MicroSeq 500 16S rDNA Bacterial Identification System, Life Technologies, Grand Island, NY, USA) according to the manufacturer’s instructions and compared nucleotide sequences using the MicroSeq ID Analysis Software. Lung samples from UME dolphins were also tested for the presence of Nocardia DNA using previously published protocols [ 31 ]. Necropsy culture swabs and tissues were also collected for classical microbial culture techniques.…”
Section: Methodsmentioning
confidence: 99%
“…12,14 By contrast, only a few reports mention this bacterium as the causative agent of disease in veterinary medicine. 2,8,16,18 Genotypic and phenotypic comparison between members of the genus Nocardia revealed that human isolates of N. cyriacigeorgica and N. asteroides type VI strains share identical partial 16S rRNA gene sequences and similar antimicrobial susceptibility. 3,14 It seems possible that bacteriologic misdiagnosis due to the genetic homology between these 2 Nocardia species may partially account for the scarcity of reported cases of N. cyriacigeorgica as the causative agent of pyogranulomatous disease in veterinary medicine.…”
Section: Research-article2014mentioning
confidence: 99%